Effects of air‐cooling on skin cells of hollow‐fiber membranes prepared via thermally induced phase separation. Issue 7 (8th September 2014) - Wu, Haoyun; Li, Lei; Li, Pingli; Yin, Qiuxiang; Chang, Heying
<x xml:space="preserve">Abstract</x> A new coarsening model was established to describe the growth of skin droplets on a hollow‐fiber membrane prepared by liquid–liquid thermally induced phase separation. Forced air‐cooling was performed to trigger the phase separation. The heat and mass transfer processes of the skin layer are considered simultaneously. With the aid of a transfer model and data from the phase diagram, the skin cell sizes could be calculated. The effects of air velocity, air temperature, and dimensions of the hollow fiber on the skin cell sizes of the isotactic polypropylene–di‐n‐butyl phthalate–dioctyl phthalate system were investigated. The growth of the skin droplets follows an exponential relationship with time, and the exponent increases with the decrease in the polymer content. All exponents are close to 1/3. The air temperature plays less important roles on the skin cell sizes as compared with those of the air velocity and fiber dimension. Calculated values of cell sizes agree well with the experimental values. POLYM. ENG. SCI., 55:1661–1670, 2015. © 2014 Society of Plastics Engineers